Land use and economic changes around EDSA-MRT stations in Quezon City - Lapena, Mary Therese T. (2004)
Any transportation project has economic and land use impacts along its corridor. For modes with specific terminals or stations, the effects are most prominent in the vicinity of these stations. This is because stations or terminals are considered points of convergence of people and therefore provides a captured market for economic activities.